Anxiety in High School Adolescents by Gender: Friend Attachment, Ineffective Coping with Stress, and Gender in Predicting Anxiety - Öner Çelikkaleli, Sezai Demir (Educational Process: International Journal, 2022)
Background/purpose – Anxiety is one of the most common mental health problems seen in children and adolescents. Based on this general framework, the first aim of the study is to reveal the prevalence of trait anxiety among adolescents and to determine whether this prevalence differs according to their gender. The second aim is to reveal whether adolescents’ ineffective coping styles with stress, friend loyalty, and gender predict trait anxiety.